Humorous interaction, language learning, and social media. Issue 1 (25th November 2019) - Chik, Alice
Abstract: The rising popularity of language learning social network websites (LLSNSs) like Duolingo and Hellolingo reconfigures traditional language learning by providing structured learning materials and spaces for social interaction among language learners. The social interactive aspects have been celebrated to be the facilitating reason to advance learning. Many of these LLSNSs also claim to have millions of active users. This is then the first time in the history of language teaching and learning that we witness a massive number of language learners gathering on the same platform for learning and interaction. On many of these LLSNSs, English learning frequently dominates. This study adopts an observational ethnographic approach to collect natural interaction between English learners of different linguistic backgrounds. Based on interaction collected from about 2, 000 threads, this paper examines the ways in which learners use multilingual resources to make sense of humorous English sentences. Findings suggest that in addition to translation, learners frequently draw on word play and popular culture on these LLSNSs to illustrate and enhance learning.